Intestinal Ciliates of Plains Zebra (Equus quagga Gmelin, 1788) in Turkey - GÜRELLİ, GÖZDE (Magnolia Press, 2023)
An investigation was carried out to identify the intestinal ciliated protozoa of the plains zebra known as Burchell’s zebra (Equus quagga burchellii Gray, 1824) living in Sasalı National Park (İzmir, Turkey) and Gaziantep Zoo (Gaziantep, Turkey) and of the plains zebra known as Grant’s zebra (Equus quagga boehmi Matschie, 1892) living in Darıca Faruk Yalçın Zoo (Darıca, Turkey). A total of 27 species and 1 morphotype belonging to 17 genera and 6 families were detected. Bundleia elongata was identified in all examined zebras, whereas Bundleia inflata, Blepharoconus benbrooki, Blepharocorys cardionucleata, Circodinium minimum, Cycloposthium bipalmatum, Ditoxum brevinucleatum, D. hamulus, and Arcosoma brevicorniger were identified only in one zebra. The average quantity of intestinal ciliates in the 9 zebras was 11.0 ± 17.0 × 104 cells mL−1. According to this study, the total number of ciliate species in the intestine of zebras increased to 51. This is the first time a report has been made on Paraisotricha colpoidea, Blepharoprosthium polytrichum, Bundleia elongata, B. triangularis, Paraisotrichopsis composita, Arcosoma brevicorniger, and A. dicorniger from zebra intestines. Moreover, A. brevicorniger was observed in binary fission for the first time.
Keywords: Turkey; Animals; Equidae; Ciliophora